2014
DOI: 10.1039/c3em00378g
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation behavior of nanodiamonds and their functionalized analogs in an aqueous environment

Abstract: The colloidal behavior of aqueous dispersions of detonation nanodiamonds (DNDs) and carboxylated nanodiamonds (DND-COOH) which were synthesized via a microwave process is presented. Both forms of DNDs were found to be relatively stable in aqueous solutions, but aggregated rapidly in the presence of mono and divalent salts. The critical coagulation concentration (CCC) values for DNDs and DND-COOH were estimated to be between 8 and 10 mM for NaCl and 7 and 8 mM for MgCl2. In general, the formation of carboxyl gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…TRDL was used to investigate the initial aggregation kinetics of f-CNT dispersions which was measured by monitoring the time-dependent increase in hydrodynamic radius (r h ). The attachment efficiency ( α ), which is the inverse of the Fuchs stability ratio commonly used in colloidal stability studies was used to quantify the aggregation kinetics (Desai et al 2014):…”
Section: Resultsmentioning
confidence: 99%
“…TRDL was used to investigate the initial aggregation kinetics of f-CNT dispersions which was measured by monitoring the time-dependent increase in hydrodynamic radius (r h ). The attachment efficiency ( α ), which is the inverse of the Fuchs stability ratio commonly used in colloidal stability studies was used to quantify the aggregation kinetics (Desai et al 2014):…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of the SWCNT agglomerates performed using DLS provided hydrodynamic diameter measurements of the nanotubes (Cheng et al, 2011; Schwyzer et al, 2013, 2012) and showed that smaller agglomerate size were obtained for the acid treated samples relative to pristine ones (Dong et al, 2013b; Jiang et al, 2009). The smaller agglomerate formation was further associated with the interplay between the Van der Waals attraction forces and the electrical repulsive forces caused by the O-rich groups present onto the individual sample according to the Schulze–Hardy rule (Desai et al, 2014; Sano et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…However, for optimal and specific drug or biomolecule loading, interactions and stability on diamond surface are still challenging tasks due to surface inhomogeneity and contamination [8]. A major obstacle to diamond particles being used in bio-systems is particle aggregation [9,10]. This process is mostly driven by graphitic or amorphous carbon structures and various oxygen related surface groups on the NDs surface which originate from their production, purification and irradiation to induce color centers.…”
Section: Introductionmentioning
confidence: 99%